Similarity between the Usher Plug and the Repeating Domain of an Ice‐adhesin: Evolution via Surface Reshaping. Issue 5 (2nd February 2017) - Kessel, Amit; Kolodny, Rachel; Ben‐Tal, Nir
Abstract: The PapC usher and MpAFP ice‐adhesin feature Ig‐like domains, which are similar in shape and sequence but are engaged in very different functions. We explore how evolution reshaped the surfaces of these two domains to fit to their respective functions. In PapC, the Ig‐like domain forms a rigid plug that seals the translocation channel in the inactive state. Upon activation, it undergoes a hinge motion, as an intact domain, to allow passage and assembly of the pili that goes through the pore. In accordance with this function, our calculations show that its surface is, in essence, electrostatically neutral, to facilitate the interaction with the PapC pore, and that this feature is evolutionarily conserved among its close homologues. On the other hand, within the context of MpAFP, the Ig‐like domain is the main repeating unit, and our calculations show that its surface features a negative electrostatic potential of unusually high magnitude. The potential is balanced by bound Ca 2+ ions. This is consistent with Ca 2+ ‐dependent secretion of unfolded MpAFP across the double membrane of the bacterium, and folding outside, where Ca 2+ concentration is high. Abstract :